2017
DOI: 10.18632/oncotarget.14865
|View full text |Cite
|
Sign up to set email alerts
|

Organ-specific isogenic metastatic breast cancer cell lines exhibit distinct Raman spectral signatures and metabolomes

Abstract: Molecular characterization of organ-specific metastatic lesions, which distinguish them from the primary tumor, will provide a better understanding of tissue specific adaptations that regulate metastatic progression. Using an orthotopic xenograft model, we have isolated isogenic metastatic human breast cancer cell lines directly from organ explants that are phenotypically distinct from the primary tumor cell line. Label-free Raman spectroscopy was used and informative spectral bands were ascertained as differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 62 publications
4
37
0
Order By: Relevance
“…The findings of the present study have implications for future research, including in‐depth mechanistic research into changes metastatic cells acquire to adapt into new environments such as organs. Previous studies conducted by Hedegaard et al and Winnard Jr et al using breast cancer isogenic cell lines have shown that this phenomenon is common, however, there are no studies in prostate cancer. Furthermore, with novel chemotherapeutic agents being introduced for the treatment of hormone‐resistant prostate cancer, it is important to develop and validate new technologies (such as Raman spectroscopy) to monitor changes in the phenotype of cells as a marker of response to these treatments.…”
Section: Resultsmentioning
confidence: 95%
“…The findings of the present study have implications for future research, including in‐depth mechanistic research into changes metastatic cells acquire to adapt into new environments such as organs. Previous studies conducted by Hedegaard et al and Winnard Jr et al using breast cancer isogenic cell lines have shown that this phenomenon is common, however, there are no studies in prostate cancer. Furthermore, with novel chemotherapeutic agents being introduced for the treatment of hormone‐resistant prostate cancer, it is important to develop and validate new technologies (such as Raman spectroscopy) to monitor changes in the phenotype of cells as a marker of response to these treatments.…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, only a few studies have attempted label-free characterization of cells for studying biological processes associated with physiological changes, disease progression, and drug response [48][49][50]. Our recent label-free Raman investigation in pellets of isogenic breast cancer cell lines that exhibit organotropism to brain, liver, lung, and spine revealed distinct metastatic organ-specific spectral signatures that were confirmed by metabolomics analysis [23].…”
Section: Introductionmentioning
confidence: 81%
“…PLS-DA was selected to accomplish discrimination between the healthy and diseased classes. PLS-DA algorithms have been shown to be effective in various disease diagnostic applications including for investigating inflammatory bowel diseases 50 , coronary heart diseases 51 , and various forms of cancer [52][53][54][55][56][57][58][59][60][61][62][63][64] , among many others. Specifically, PLS-DA is a supervised technique which is used to predict categorical variables.…”
Section: Partial Least Squares Discriminant Analysis (Pls-da)mentioning
confidence: 99%